Novel Surgical Approach for Fingertip Deformity: Reconstruction of a Small Finger Hook Nail in a Child Using a Hypothenar Flap and Distal Phalanx Osteotomy - Caleb Bercu, BA; Antoun Bouz, MD; Sarah Stavros, MD; Weston Thomas, PA-C; Aaron Berger, MD, PhD (Journal of Hand Surgery Global Online)
Hook nail deformity generally occurs after traumatic amputation of the distalmost extent of the finger. The nail bed then extends over the tip and occasionally onto the volar aspect of the digit. An absence of distal support leads to volar hooking of the nail, a cosmetic deformity that can be painful and interfere with function. Treatment of this deformity is typically conservative, as there is little consensus on ideal treatment, and most techniques described in the literature are complex. We present a novel technique for the treatment of hook nail (and other fingertip) deformity in the small finger using a hypothenar flap combined with distal phalanx osteotomy.